2021
DOI: 10.1016/j.heliyon.2021.e07636
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the role of Plant Growth Promoting Rhizobacteria in suppressive soils against Fusarium oxysporum f.sp. cubense based on metagenomic analysis

Abstract: Fusarium oxysporum f.sp. cubense (Foc) is a soil-borne pathogen causing fusarium wilt banana disease. Management of soil-borne disease generally required the application of toxic pesticides or fungicides strongly affect the soil microbiomes ecosystem. Suppressive soil is a promising method for controlling soil-borne pathogens in which soil microbiomes may affect the suppressiveness. The comparative analysis of microbial diversity was conducted from suppressive and conducive so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Microbiome‐based studies have shown an abundance of various PGPR communities in disease suppressive soils than conducive soils. For example, several rhizobacteria belonging to Actinobacteria, Acidobacteria, Bacteroidetes, Betaproteobacteria, Rhizobiales, Burkholderiales, Bradyrhizobiaceae, Methylobacteriaceae, have been found as major predictors for soil suppressiveness against Fusarium oxysporum (Nisrina et al, 2021; Trivedi et al, 2017; Zheng et al, 2020). In addition, higher Zn/Mn and phosphate transport systems of Pseudomonas and Burkholderia having a role in siderophore and P solubilization were linked with the suppressiveness of soils (Nisrina et al, 2021).…”
Section: Rhizobacteria‐ Mediated Disease Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiome‐based studies have shown an abundance of various PGPR communities in disease suppressive soils than conducive soils. For example, several rhizobacteria belonging to Actinobacteria, Acidobacteria, Bacteroidetes, Betaproteobacteria, Rhizobiales, Burkholderiales, Bradyrhizobiaceae, Methylobacteriaceae, have been found as major predictors for soil suppressiveness against Fusarium oxysporum (Nisrina et al, 2021; Trivedi et al, 2017; Zheng et al, 2020). In addition, higher Zn/Mn and phosphate transport systems of Pseudomonas and Burkholderia having a role in siderophore and P solubilization were linked with the suppressiveness of soils (Nisrina et al, 2021).…”
Section: Rhizobacteria‐ Mediated Disease Suppressionmentioning
confidence: 99%
“…For example, several rhizobacteria belonging to Actinobacteria, Acidobacteria, Bacteroidetes, Betaproteobacteria, Rhizobiales, Burkholderiales, Bradyrhizobiaceae, Methylobacteriaceae, have been found as major predictors for soil suppressiveness against Fusarium oxysporum (Nisrina et al, 2021; Trivedi et al, 2017; Zheng et al, 2020). In addition, higher Zn/Mn and phosphate transport systems of Pseudomonas and Burkholderia having a role in siderophore and P solubilization were linked with the suppressiveness of soils (Nisrina et al, 2021). Similarly, microbial communities ( Pseudomonas in Proteobacteria and Streptomyces in Actinobacteria ) harbouring nonribosomal peptide (NRP)‐synthesizing genes were abundant in the suppressive soil than in the conducive soils to banana Fusarium wilt disease (Zhao et al, 2018).…”
Section: Rhizobacteria‐ Mediated Disease Suppressionmentioning
confidence: 99%
“…Second, 66 bacterial species known to have strains with antagonistic activities against plant pathogens (BCA candidates) were also identified. The bacterial orders and BCA candidates observed resemble those in the suppressive soils from other environments [ 21 , 59 , 60 , 61 , 62 ]. They are important components of a healthy soil microbiome [ 3 , 4 , 63 , 64 ], and likely have contributed to the decline of the Cps population in these garden soils [ 33 ].…”
Section: Discussionmentioning
confidence: 76%
“…Specifically, Pseudomonas , Bacillus , Paenibacillus , and Streptomyces species are well known to inhibit the formation and germination of microsclerotia by Verticillium spp. or increase their mortality [ 80 , 81 , 82 , 83 ], by producing volatile organic compounds [ 81 ] or chitin lysis enzymes [ 62 , 79 ]. Some of the same genera identified in this study likely have contributed to the decline of Cps , which also produces microsclerotia for survival in soils [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, for instance, the metagenome analysis pipeline DIAMOND+MEGAN6 (26, 27, 28, 29, 30) can be used, as it comes up with the conservative read alignment approach against NCBInr proteins that are further mapped to NCBI (31) or GTDB (32) taxonomy and various functional classifications, including KEGG. For example, Nisrina and coworkers applied a MEGAN approach for PGPT screening of PGPBs in fungi suppressive soils (33). Recently, the AnnoTree assignment approach was added to MEGAN, that showed higher accuracy especially for environmental samples like soil, addressing a huge amount of uncultured strains as it relies on additional protein sequences derived from metagenome-assembled-genomes (MAGS) (34, 35).…”
Section: Introductionmentioning
confidence: 99%